ATP como modulador do sistema purinérgico e inflamação e status redox em pacientes com melanoma - Manica, Aline (2019)
Melanoma is a type of skin cancer, formed in melanocytes, cells that produce the pigment melanin. The melanocytes of the epidermis are the most common places of melanoma’s origin; however, it can be also developed in melanocytes of the eye, mucous surfaces, respiratory tract, genitourinary and gastrointestinal tract. It is one of the most aggressive known neoplasms, with high proliferation capacity, stimulation of angiogenesis, involvement of successive levels of the dermis and generation of metastases, by lymphatic or hematogenous route. The frequency of new cases increases every year, especially in the young population of southern Brazil, becoming an important public health problem. Thus, considering that purinergic signaling, inflammatory response and oxidative stress are important pathways that influence the initiation, progression and development of melanomas, and that the geographical region of study chosen has high prevalence of this type of cancer, this study aimed to evaluate the effects of ATP on the purinergic system, inflammatory markers and oxidative stress in patients with melanoma to elucidate the changes in the tumor microenvironment and understand the pathophysiology of melanoma, whereas they may justify the high aggressiveness of this type of cancer. Our work consisted of collecting venous blood from patients with melanoma before and after surgical procedure of removing the tumor and a group of control patients of the study. All patients were selected and monitored by a medical team. Enzymatic analyses, nucleotide quantification, inflammatory and oxidative parameters and culture of polymorphonuclear cells of peripheral blood were performed. Regarding ethical aspects, this study was approved by the ethics committee of the Federal University of the Southern Frontier, under assessment number 822,782. The results found showed that patients with melanoma after surgical removal presented a reduction in the hydrolysis of nucleotides. In contrast, pre-surgery or untreated patients had an increase in ATP, ADP and AMP hydrolysis. Such alterations would be promoting an increase in extracellular ATP, which was confirmed by its quantification in the patient’s serum. In addition, patients with melanoma after surgical removal of the tumor presented a decompensated inflammatory environment, evidenced by increased interleukins IL-2, IL-4, IL-6, TNF, IFN-Y, IL- 17A, IL-10 and increased ADA activity. Regarding the parameters of oxidative stress, it was observed a reduction in oxidative damage and an increase in antioxidant defenses after the surgical process, confirming the effectiveness of the surgical process for localized lesions. Our main hypothesis concerns the signaling, immunosuppressive and oxidizing effects of extracellular ATP, both in vivo and in vitro analyses. We conclude through this thesis that ATP is an important molecule involved in the process of melanomagenesis and tumor progression and may serve as a tool in clinical practice. Thus, by controlling their levels in the cells, one can improve the prognosis for patients affected by this cancer of high lethality and aggressiveness.